The SEC As a Lawmaker: Choices About Investor Protection in the Face of Uncertainty - Donald C. Langevoort (Washington University Law Review, 2006)
A problem that has dominated much of recent corporate legal scholarship is one of political economy: what drives (and constrains) the production of corporate law? As used here, “corporate law” refers to the body of regulation dealing with the allocation of power, rights, and responsibilities relating to management and control of the corporation—a rough description that includes many of the disclosure-related demands of federal securities regulation. My paper will look at the portion of corporate-securities law that is produced by the Securities and Exchange Commission (SEC). Put simply, what drives and constrains the SEC as a federal corporate lawmaker?
Keywords: Antitrust law; Federal government; Political questions & amp; judicial power; Administrative law; Cost effectiveness; Uncertainty – Economic aspects; United States; Securities & amp; Exchange Commission; Cost benefit analysis; Disclosure (Securities law); Federalism